Ramsey Hunt syndrome in the child: case report and treatment approach - A. K. Shakaryan; I. V. Mitrofanova; S. V. Shakhgildyan (Нервно-мышечные болезни)
Herpes zoster is a manifestation of the reactivation of an infection after chickenpox. One of the manifestations of herpes zoster is Ramsey Hunt syndrome, which develops when the ganglion of the VII pair of cranial nerves is involved in process. Diagnosis of Ramsey Hunt syndrome is often based on a combination of a rash in the outer ear and peripheral paresis of the facial muscles. The article describes a rare clinical case of herpes zoster in a child without clinical signs of immunodeficiency, with the development of unilateral paralysis of the facial muscles, pleocytosis in the cerebrospinal fluid. Therapy was performed with a combination of acyclovir and high doses of methylprednisolone with a good clinical effect. It is first mentioning of deviations in the immune status (decreased concentration of the number of markers of naive T‑lymphocytes (TREC)) were revealed, which could be associated with the development of herpes zoster in a child.